Investigation on optical temperature sensing behaviour via Ag island-enhanced luminescence doped β-NaGdF4:Yb3+/Tm3+ films/microfibers. Issue 58 (11th November 2021) - Shahzad, Muhammad Khuram; Farooq, Usman; Raza, Adil; Abbas, Ghulam; Ikram, Muhammad; Zhang, Yundong
Abstract : In this study, silver (Ag) island modified up-conversion nano-particle thin films were prepared via electrostatic layer by layer (LBL) and spin coating techniques. Abstract : In this study, silver (Ag) island modified up-conversion nano-particle (NaGdF4 :Yb 3+ /Tm 3+ ) thin films were prepared via electrostatic layer by layer (LBL) and spin coating techniques. The spectroscopic results indicated that adding Ag nanoparticles could significantly enhance the up-conversion emission of NaGdF4 :Yb 3+ /Tm 3+ thin films at 452 nm and 476 nm. The maximum enhancement factor of ∼15.6 was reached at 476 nm. Furthermore, we prepared microfibers from upconverting nanoparticles solution, the application of microfibers as active and passive waveguides was analyzed by observing the performance of microfibers with and without Ag under 980 nm excitation of the laser source. The fluorescence intensity ratio (FIR) method was adopted to evaluate microfiber sensitivity. The intensity-based temperature sensitivity of blue emission from a single microfiber containing up-conversion nanomaterials (NaGdF4 :Yb 3+ /Tm 3+ ) and Ag nanoparticles reached up to 0.018 K −1 at 310 K compared to 0.0029 K −1 in Ag-free microfiber. Our results suggest that the novel material can be used to construct new nano-thermometers, useful both in biological experiments as well as industrial research.